A practical review of the neuropathology and neuroimaging of multiple sclerosis. Issue 4 (23rd March 2016) - Matthews, Paul M; Roncaroli, Frederico; Waldman, Adam; Sormani, Maria Pia; De Stefano, Nicola; Giovannoni, Gavin; Reynolds, Richard
Abstract : The variability in the severity and clinical course of multiple sclerosis (MS) has as its basis an extreme heterogeneity in the location, nature and extent of pathology in the brain and spinal cord. Understanding the underlying neuropathology and associated pathogenetic mechanisms of the disease helps to communicate the rationale for treatment and disease monitoring to patients. Neuroimaging is an important tool for this: it allows clinicians to relate neuropathological changes to clinical presentations and to monitor the course of their disease. Here, we review MS neuropathology and its imaging correlates to provide a practical guide for using MRI to assess disease severity and treatment responses. This provides a foundation for optimal management of patients based on the principle that they show 'no evidence of disease activity'.